ANALISIS DETERMINAN KINERJA KEUANGAN PADA DINAS PENDIDIKAN KABUPATEN YAHUKIMO PROVINSI PAPUA - mugiati, Mugiati; Wadjo, Muhammad Amin; Aditama, Muhammad Irfan (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This study aims to examine and analyze the influence of budget preparation, budget expenditure process, budget preparation, and budget supervision on the Financial Performance of the Yahukimo Regency Education Office and to examine and analyze the factors that have the most dominant influence on the performance of the Yahukimo Regency Education Office. The data collection methods used were observation, interviews and questionnaires. Data were analyzed descriptively and quantitatively using Multiple Linear Regression Analysis. The number of samples in this study was 78 respondents. The results of the study indicate that: Partially, Budget Factors (X1), Budget Expenditure Process (X2), and Budget Use (X3) have an effect on the Performance of the Yahukimo Regency Education Office, while Budget Control (X4) does not have a significant effect on the Performance of the Yahukimo Regency Education Office. Simultaneously, Budget Factors (X1), Budget Expenditure Process (X2), Budget Use (X3), and Budget Control (X4) have a significant effect on the Performance of the Yahukimo Regency Education Office. The variable that has the most dominant influence on the Performance of the Yahukimo Regency Education Office among the four variables above is the Budget Factor.